Indoor Perovskite Photovoltaics for the Internet of Things—Challenges and Opportunities toward Market Uptake. Issue 38 (25th August 2021) - Polyzoidis, Christos; Rogdakis, Konstantinos; Kymakis, Emmanuel
Abstract: The high‐power conversion efficiency of flexible perovskite photovoltaics (PPV) at low light environment and their low‐cost manufacturing processes, render PPV superior to conventional rigid photovoltaics targeting indoor applications. However, various parameters related to materials, architecture, processing, and indoor characterization need to be optimized further toward improving indoor PPV (iPPV) efficiency, stability, and ecotoxicity. This work provides an overview of the recent progress, trends, and challenges in the field and suggests a holistic approach toward a viable design and integration of iPPVs into Internet of Things (IoT) platforms without any compromise on safety and cost effectiveness. The key impact of selecting proper materials and fabrication techniques, as well as optimizing the active area and architecture is described. Certain peculiarities of the indoor lighting conditions are discussed that can be addressed by proper simulation tools, including the understanding of the charge‐transfer mechanism, the diversification of the lamp types, as well as identifying the requirements for the production, standardization, and installation of iPPVs associated with IoT devices. A multidimensional engineering approach that considers aspects of architecture, light technology, load specifications, materials, processing, safety and cost, is proposed as a path toward accelerating iPPV market uptake for households, businesses, wearables and Industry 4.0 applications. Abstract : This review discusses all crucial scientific, commercial, and product development guidelines toward the viable commercialization of indoor perovskite photovoltaics that supply power for Internet of Things systems. Thus, it may be used as a tool from both the product designer and the researcher side who need an in‐depth and interdisciplinary approach that relies on state‐of‐the‐art reports.